145 ADVANTAGES OF MINIMALLY INVASIVE TRANSMEDIASTINAL ESOPHAGECTOMY IN ELDERLY PATIENTS WITH ESOPHAGEAL CANCER. (17th September 2021) - Nakamura, Kei; Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Kudo, Michihiro; Shimizu, Hiroki; Arita, Tomohiro; Kosuga, Toshiyuki; Morimura, Ryo; Kuriu, Yoshiaki; Ikoma, Hisashi; Kubota, Takeshi; et al.
Abstract: : Esophagectomy for esophageal cancer (EC) is one of the most invasive surgical procedures and, especially for elderly patients, postoperative respiratory complication (PRC) is still frequent and life-threatening. We started esophagectomy by a laparoscopic transhiatal approach in 2009, and single-port mediastinoscopic cervical approach in 2014. Nowadays, we have performed total mediastinal lymph node dissection without thoracic approach. The purpose of this study was to evaluate transmediastinal esophagectomy (TME) for the prevention of PRC in elderly patients. Methods: 1) Patients with EC performed TME (n = 238) were compared with those performed the right thoracotomy (n = 185). 2) Outcomes of TME for elderly patients (75 years and older, n = 48) was evaluated by comparing with non-elderly patients (n = 190). 3) Elderly patients performed subtotal esophagectomy were divided into 2 groups according to the presence (n = 12) or absence (n = 51) of PRC. The two groups were compared about clinicopathological factors, and risk factors of PRC were analyzed. Results: 1) Percentage of elderly patients was higher in TME group (20.2% vs 8.1%). The operative time and bleeding were decreased by TME. The number of resected LNs and pR0 rate were not different between two groups. In TME groups, the occurrence of PRC was significantly reduced (10.1% vs 28.1%). 2) 81.3% of elderly patients were able to extubation on 0POD, and there was no significant difference in PRC between two groups. 3) Univariate analysis showed that surgical approach was significantly different between two groups. Multivariate analysis showed that thoracotomy was the strongest risk factor of PRC for elderly patients. Conclusion: This study showed that our surgical procedure was less invasive during operation and resulted in a safe en-bloc mediastinal lymph node dissection. For elderly patients, TME was the effective minimally invasive approach and was able to reduce the occurrence of PRC.